Risk - A Multidisciplinary Introduction - Klüppelberg, Claudia; Straub, Daniel; Welpe, Isabell M. (Springer eBooks, 2014)
This is a unique book addressing the integration of risk methodology from various fields. It stimulates intellectual debate and communication across disciplines, promotes better risk management practices and contributes to the development of risk management methodologies. Book chapters explain fundamental risk models and measurement, and address risk and security issues from diverse areas such as finance and insurance, health sciences, life sciences, engineering and information science. Integrated Risk Sciences is an emerging field, that considers risks in different fields aiming at a common language, and at sharing and improving methods developed in different fields. Readers should have a Bachelor degree and at least one basic university course in statistics and probability. The main goal of the book is to provide basic knowledge on risk and security in a common language; the authors have taken particular care to ensure that each chapter can be understood by doctoral students and researchers across disciplines. Each chapter provides simple case studies and examples, open research questions and discussion points, and a selected bibliography inviting the reader to further studies.